The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1590/s1677-54492007000300005
|View full text |Cite
|
Sign up to set email alerts
|

The origin of the inferior phrenic artery: a study in 32 South Indian cadavers with a review of the literature

Abstract: BACKGROUND: Considering the paucity of information presently available concerning inferior phrenic arteries, a more definitive study seemed appropriate and necessary, both for its potential clinical applications and to provide additional data to contemporary anatomical literature. OBJECTIVE: Most anatomical textbooks of gross anatomy offer very little information concerning the anatomy and distribution of the inferior phrenic artery (IPA). For that reason, the origin of the IPA has been studied and the availab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…The inferior phrenic arteries (IPA) of right and left side arise as lateral branch from the abdominal aorta, but in the present case, the left IPA arises from the LGA also reported by Pulakunta et al (2007) and Silveira et al (2009). During hepato-cellular carcinoma (HCC), the IPA is the most frequent artery establishes the extra-hepatic collateral circulation because this artery is in close contact between the posterior part of liver and diaphragm at the bare area of the liver.…”
Section: Discussionmentioning
confidence: 54%
“…The inferior phrenic arteries (IPA) of right and left side arise as lateral branch from the abdominal aorta, but in the present case, the left IPA arises from the LGA also reported by Pulakunta et al (2007) and Silveira et al (2009). During hepato-cellular carcinoma (HCC), the IPA is the most frequent artery establishes the extra-hepatic collateral circulation because this artery is in close contact between the posterior part of liver and diaphragm at the bare area of the liver.…”
Section: Discussionmentioning
confidence: 54%
“…According to Nayak SR. [15] the left inferior phrenic artery was seen to take origin from the celiac artery as its first branch. In another study done by Pulakunta T. [16] the inferior phrenic artery showed a variant origin in four out of 32 cases. It was seen to arise directly from the celiac trunk in two cases and there was one case arising from the left gastric artery and another from the right renal artery.…”
Section: Observationmentioning
confidence: 83%
“…They also noted alternative origins (left gastric, hepatic, superior mesenteric, and spermatic), stating that such origins occurred with <4% frequency on either the right or left side. Pulakunta T et al 13 did a study on 32 cadavers observed the origin of the inferior phrenic arteries from the celiac trunk in two specimens (6.25%), one from the left gastric artery (3.125%) and one from the right renal artery (3.125%) out of the 32 cadavers. In the remaining 28 specimens it had its normal origin from the abdominal aorta.…”
Section: Discussionmentioning
confidence: 96%
“…17 Extensive knowledge of all possible variations of inferior phrenic artery origin will provide valuable data to researchers, clinicians and anatomists alike. These data will useful for the management of liver transplants and biliary tract surgery, 13 enhancing the understanding of both the specific anatomy of the inferior phrenic arteries as well as their potential significance in supplying hepatocellular carcinomas and other liver tumors, primary or metastatic, such as cholangiocarcinoma, hepatoblastoma and subcapsular adenoma. 18 It is also useful in evaluating the efficacy and safety of Tans catheter oily chemo embolization technique via inferior phrenic artery, discussion and treatment of other hepatic, suprarenal or even diaphragmatic lesions.…”
Section: Pick and Ansonmentioning
confidence: 99%
See 1 more Smart Citation